Comparative assessment of implicit and explicit finite element solution schemes for static and dynamic civilian aircraft seat certification (CS25.561 and CS25.562) - Gulavani, Omkar Vitthal (Cranfield University, 2013)
Due to the competitive nature of airline industry and the desire to minimise aircraft weight, there is a continual drive to develop lightweight, reliable and more comfortable seating solutions, in particular, a new generation slim economy seat. The key design challenge is to maximise the “living space” for the passenger, with strict adherence to the ‘Crash Safety Regulations’. Cranfield University is addressing the needs of airliners, seat manufactures and safety regulating bodies by designing a completely novel seat structure coined as “Sleep Seat”. A generous angle of recline (40 degree), movement of “Seat Pan” along the gradient, fixed outer shell of the backrest, and a unique single “Forward Beam” design distinguishes “Sleep Seat” form current generation seats. It is an ultra-lightweight design weighing 8kg (typical seat weight is 11kg). It has to sustain the static (CS 25.561) and dynamic (CS25.562) “Emergency landing” loads as specified by “Certification Specifications (CS). Apart from maintaining structural integrity; a seat-structure must not deform, which would impede evacuation, should absorb energy so that the loads transferred to Occupants are within human tolerance limits and should always maintain survivable space around the Occupant. All these parameters, which increase a life-expectancy in a ‘survivable’ crash, can be estimated using either experimental testing or virtual simulation tools such as “Finite Element Analysis (FEA). Design of the “Sleep Seat” is still in its conceptual phase and therefore experimental testing for all the design iterations involved is unrealistic, given a measure of the costs and timescales involved. Therefore focus of research is to develop practical and robust FE methodologies to assess static and dynamic performances of a seat-structure so as to compare different design concepts based on their strength, seat interface loads (a limit defined by strength of aircraft-floor), maximum deformations and cross-sectional forces ... [cont.].
Keywords: Certification By Analysis; LSDYNA V9.71 R4.2.1; Abaqus (Research) 6.9-3; Optistruct; Damaged floor condition; Aircraft Seat